Improving Critical Thinking Aspects with Podcast Media - Akhmad Khasbullah; Azky Izza Azzami; Bachtiar Fahmi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
Podcasts are used as a medium to improve critical thinking skills. Students often feel bored and tired when having to read text as a source of information. The purpose of this study is to analyze how podcasts improve critical thinking. This study used a qualitative research method with a library research approach. The impact on improving students' digital literacy skills shows that podcasts can improve verbal skills, enrich knowledge, enhance critical thinking skills, and broaden horizons.